Kshemankari - Temples of India Project Team (Jio Institute, 2024)
An eight-armed deity is depicted standing in samabhanga (upright posture) on a lotus beneath which are two addorsed lions. The deity holds a shield in the upper left hand; the remaining hands are broken. A halo is present behind her head. A female attendant stands on the right. Stylistically similar to those seen at Ambika Temple in Jagat (dated 10th century CE).